Impact of fire on leaf nutrients, arthropod fauna and herbivory of native and exotic eucalypts in Kings Park, Perth, Western Australia - Radho-Toly, S.; Majer, Jonathan; Yates, C. (2001)
The vegetation of Kings Park, near the centre of Perth, Western Australia, once had an overstorey of Eucalyptus marginata (jarrah) or Eucalyptus gomphocephala (tuart), and many trees still remain in the bushland parts of the Park. Avenues and roadsides have been planted with eastern Australian species, including Eucalyptus cladocalyx (sugar gum) and Eucalyptus botryoides (southern mahogany), both of which have become invasive. The present study examined the effect of a recent burn on the level of herbivory on these native and exotic eucalypts. Leaf damage, shoot extension and number of new leaves were measured on tagged shoots of saplings of each tree species in unburnt and burnt areas over an 8-month period. Leaf macronutrient levels were quantified and the number of arthropods on saplings was measured at the end of the recording period by chemical knockdown. Leaf macronutrients were mostly higher in all four species in the burnt area, and this was associated with generally higher numbers of canopy arthropods and greater levels of leaf damage. It is suggested that the pulse of soil nutrients after the fire resulted in more nutrient-rich foliage, which in turn was more palatable to arthropods. The resulting high levels of herbivory possibly led to reduced shoot extension of E. gomphocephala, E. botryoides and, to a lesser extent, E. cladocalyx. This acts as a negative feedback mechanism that lessens the tendency for lush, post-fire regrowth to outcompete other species of plants. There was no consistent difference in the levels of the various types of leaf damage or of arthropods on the native and the exotic eucalypts, suggesting that freedom from herbivory is not contributing to the invasiveness of the two exotic species.